Relationship between motivation, satisfaction, and organizational commitment among scout volunteers in East Kalimantan, Indonesia - Rahmawati, Yeni (2014)
Organizational commitment is considered as fundamental element in any nature of organization. Majority studies have been conducted to expose organizational commitment among profit organization, oppositely, similar study in nonprofit organization tend to be lacking. Therefore, this study was conducted to determine the level of organizational commitment within nonprofit organization that also linked to non formal element. In addition, as regards to extension education, the general purpose of this study was to determine relationship between motivation, satisfaction, and organizational commitment among scout volunteers in East Kalimantan, Indonesia. The sample consisted of 207 scout volunteers including 126 male and 81 female ranges aged 17 to 47 years old. In the current study, the participants were recruited by using random sampling technique. By using self-administered questionnaire, the participants completed the demographic information and three part of mind questionnaire related to the study (motivation, satisfaction, and organizational commitment). The present study used a quantitative research to examine relationship among variables. Several objectives were created to fulfill the study namely determine the level for overall variables, determine relationship among motivation, satisfaction, and organizational commitment, and determine the best predictor of the dimension from independent variable (motivation and satisfaction) for organizational commitment. Data analysis included frequencies, percentages, mean scores, Pearson correlations, and multiple linear regressions. The statistic data were computed by using SPSS at alpha level .05 The result indicated that there was a significant relationship between overall motivation (r = .468), satisfaction (r = .298) and organizational commitment. Majority dimensions of motivation and satisfaction had positive relationship towards organizational commitment. Moreover, understanding (r = .436) was considered as the best predictor affecting organizational commitment rather than other dimensions (career, social, value, enhancement, protection, organizational support, and group integration). Oppositely, in term of satisfaction dimension, participation efficacy and empowerment did not have significant correlation with organizational commitment. The finding indicated that this study established the relationship between motivation, satisfaction, and organizational commitment within scout volunteers in East Kalimantan, Indonesia. Therefore, it has implication especially for the scout volunteers and other volunteer workers. The result of the current study may involve in various volunteers related such as social volunteers, religious volunteers, health volunteers, sport volunteers, etc. Besides that, future research is expected to be able to conduct similar research by adding the other elements as new variable to enlarge and expand volunteerism as non-profit sector. Furthermore, future research is expected to relate between volunteer activities and others extension program to support non formal education especially for youth development thus it will be able to provide more contribution for the extension education field.